PENGARUH JENIS INDUSTRI, KEPEMILIKAN MANAJERIAL, OPERATING PROFIT MARGIN DAN DIVIDEND PAYOUT RATIO TERHADAP PERATAAN LABA PADA PERUSAHAAN YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2012-2014 - Nazira, Cut Fatimah; Ariani, Nita Erika (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The objectives of this research are to examine (1) the effect of industrial type, managerial ownership, operating profit margin, and dividend payout ratio simultaneously on income smoothing, and (2) the effect of industrial type, managerial ownership, operating profit margin, and dividend payout ratio partially on income smoothing.The method used in this research is purposive sampling method. The sample of this research is company listed in Indonesia Stock Exchange during 2012-2014. The analysis method used in the research is logistic regression.The result of this research are (1) industrial type, managerial ownership, operating profit margin, and dividend payout ratio simultaneously have an effect on the income smoothing, (2) managerial ownership, operating profit margin, dividend payout ratio partially have affect the income smoothing and, (3) industrial type have not an effect on the income smoothing.Keywords: industrial type, managerial ownership, operating profit margin, dividend payout ratio and income smoothing.